Gathering Sensitive Data in Organizations - HOSSEINI, JAMSHID C.; ARMACOST, ROBERT L. (The American behavioral scientist (Beverly Hills), 1993)
Maintains that the need for gathering sensitive information frequently arises in planning and implementing organizational surveys. Describes methods of designing the instrument format and the mode of data collection. Provides a description and process summary of the Randomized Response Technique (RRT). (CFR)